Binocular Diplopia: A Possible Adverse Effect of Fluoroquinolone Therapy - Mariama Touray; Victoria Ando; Erwin Samutelela; Jean-Philippe Zuber (Case Reports in Ophthalmological Medicine)
The adverse effects of fluoroquinolones are yet to be fully elucidated. We present an interesting case of a 41-year-old male with binocular diplopia most likely induced by the use of a fluoroquinolone antibiotic.